Study on the synergistic effect of NOx and CO2 emission reduction in the industrial sector of Guangzhou - Qin, Xingcun; Xie, Pengcheng; Liao, Cuiping (Frontiers in Environmental Science, 2025)
IntroductionAs a major source of pollutant and CO2 emissions, the industrial sector faces the dual challenge of pollution control and carbon reduction. Accurately identifying the synergy between pollutant and carbon emissions in different regions’ industrial sectors is crucial for developing regional policies for coordinated pollution reduction and carbon abatement.MethodsThis study takes Guangzhou as a case study to quantitatively assess the synergistic effect of NOx and CO2 emissions reduction in its industrial sector. First, the LMDI decomposition method was applied to analyze the factors influencing the change in NOx emissions in Guangzhou’s industrial sector. Next, the CFGLS model was used to quantify the synergistic effect between NOx and CO2 emissions. Finally, a robustness check was conducted on the results.Results and discussionThe findings indicate that the synergistic effect in carbon reduction is the most significant driver of NOx reduction in Guangzhou’s industrial sector, with a 10,000-ton reduction in CO2 emissions leading to a 0.4-ton decrease in NOx emissions. The interaction effect analysis shows that increasing the use of natural gas and reducing energy intensity do not amplify this synergy. The results could provide valuable insights for coordinated pollution reduction and carbon abatement policies designing in Guangzhou’s industrial sector.